Educational and Cultural Regeneration of Modern Spain: Monarchical Reforms in Education and the Role of the Enlightenment Bishops at Eighteen Century - Raquel POY CASTRO (Cuadernos Dieciochistas)
In the 18th century the church of Spain gradually diminished its extensive powers of self-government, while remaining the monopoly of education. This period was marked by the monarchical revival and the alliance between church and State. The crown nominates diocesan bishops and the church of Spain is committed to the goal of a renewed and modern nation. The 18th century saw the rise of an enlightenment Bishops movement, with its emphasis on the recovery of the Spanish catholic tradition, and the renaissance of the educational and cultural institutions.